1984
DOI: 10.1152/ajpheart.1984.246.2.h207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on uterine blood flow in the pregnant Pygmy goat

Abstract: Pygmy goats in the last third of pregnancy were trained to walk on a treadmill at rates up to 2.0 mph and up an inclination of 0-15 degrees. Electromagnetic flowmeters were placed unilaterally on a uterine artery, and measurements were made while the goats were standing quietly on the treadmill and during 5 min of exercise. Blood flow fell during exercise in all five animals studied, and this reduction was proportional to the level of exertion. At the highest level of exercise that these animals would voluntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…Animal studies suggest decreased uterine blood flow during physical activity (5-8), but studies in women are inconclusive (9-11). Several studies have reported an increase in fetal heart rate during maternal physical activity (12-16), although changes in fetal heart rate may occur in response to maternal epinephrine and may not reflect a decrease in oxygen (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest decreased uterine blood flow during physical activity (5-8), but studies in women are inconclusive (9-11). Several studies have reported an increase in fetal heart rate during maternal physical activity (12-16), although changes in fetal heart rate may occur in response to maternal epinephrine and may not reflect a decrease in oxygen (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…That study, however, has been criticised because it used a supine position. Although some animal experiments (ewes, goats) showed unchanged uterine blood flow [9,27], most investigations showed a decrease in uteroplacental blood flow proportional to the level and duration of exercise [6,7,18,20]. Although a drop in fetal Po 2 was noticed [6,10,21], certain compensatory mechanisms counteract the reduction in blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although a drop in fetal Po 2 was noticed [6,10,21], certain compensatory mechanisms counteract the reduction in blood flow. These mechanisms include a redistribution a blood flow within the uterus favoring placental over nonplacental blood flow [9,18], an increase in uterine oxygen extraction and thus maintainance of uterine oxygen consumption [6,7,10] and an increase of hemoglobin and hematocrit within minutes after exercise begins, thus improving oxygen supply to the uterus [6,29]. The latter mechanism also occurs in humans within a few minutes [15], Rather difficult to interpret are our findings of a decrease in resistance in the umbilical artery.…”
Section: Discussionmentioning
confidence: 99%
“…Some animal studies have found that severe exertion during pregnancy is associated with increased fetal mortality and decreased fetal weight [Terada, 19741. The role of fetal anoxia in adverse reproduction outcomes associated with exposures is suggested by studies finding that uterine blood flow decreases with exercise [Morris et al, 1956;Hohimer et al, 1984;Clapp, 19801. However, other investigators have found no decrease in uterine blood flow with exercise [Orr et al, 19721.…”
Section: Physical Exertionmentioning
confidence: 99%
“…However, other investigators have found no decrease in uterine blood flow with exercise [Orr et al, 19721. More significantly, several investigators have described a redistribution of uterine flow during exercise that favors the placenta, such that any decreases in uterine flow are confined to the myometrium, while placental flow is preserved [Hohimer et al, 1984;Curet et al, 19761. Voluntary exercise is well tolerated by some women during pregnancy. Collings et a1 [1983] studied women who exercised three times weekly during the second and third trimesters, attaining average heart rates of 152 beats per minute (65-70% maximum).…”
Section: Physical Exertionmentioning
confidence: 99%